International environmental agreements under endogenous uncertainty - Nkuiya, Bruno (2014)
This paper explores the implications of the possibility of a shift in environmental damages on the participation in environmental treaties. Using a two-period model where the probability of a regime shift increases in the first-period pollution stock, we examine the issue of coalition formation under both fixed and dynamic membership. Our analysis suggests that endogenous uncertainty may increase participation. We find that full cooperation may be sustained, but only in the presence of endogenous uncertainty. Interestingly, when the shift in the environmental damage is large enough, the model provides a way to solve the “puzzle of small coalitions” found in the literature related to international environmental agreements. We also find that in period 1 (period 2) endogenous uncertainty leads to a lower (higher) pollution stock under dynamic membership as compared to the fixed membership case.